New Thorium Isotope Ratio Measurements in Silicate Reference Materials: A‐THO, AGV‐2, BCR‐2, BE‐N, BHVO‐2 and BIR‐1. Issue 2 (29th October 2015) - Carpentier, Marion; Gannoun, Abdelmouhcine; Pin, Christian; Sigmarsson, Olgeir
Abstract : A two‐step Th isolation protocol, involving micro‐columns of TRU‐Spec extraction chromatography material and AG1 resin, was evaluated. The MC‐ICP‐MS procedure included 232 Th tailing characterisation and correction, and calibrator bracketing using an in‐house standard solution (ThS1) to correct for instrumental mass bias and Faraday cup to secondary electron multiplier relative gain. Repeated analyses of reference solutions (UCSC Th 'A', WUN, OU Th 'U', IRMM‐36) were consistent with published data. Six reference materials (A‐THO, BCR‐2, AGV‐2, BHVO‐2, BE‐N and BIR‐1) were processed. The average 230 Th/ 232 Th values obtained for these samples are in excellent agreement with published data. In addition, we report the first 230 Th/ 232 Th values for BE‐N and BIR‐1. The intermediate precisions for rock samples ranged from ± 0.24 to ± 0.49% (2 RSD) and were similar to those achieved for synthetic solutions, thereby supporting the overall validity of the chemical separation, data acquisition and reduction procedures. Counting statistics on the 230 Th isotope was the most significant source of uncertainty. The intermediate precision of the mean 230 Th/ 232 Th for the Th‐depleted BIR‐1 (5.64 × 10 −6 ± 0.27%, 2 RSD) is in the range of the analyses of other reference materials analysed in this study. Key Points: A two‐step Th isolation protocol was evaluated. Measurements were made using MC‐ICP‐MS on an in‐house standard solution (ThS1). Several reference materials and synthetic solutions were investigated and the first 230 Th/ 232 Th values for BE‐N and BIR‐1 are reported.